Research of the Algorithm for Robot Workspace Boundary Extraction - Cui Zhihong; Diao Yan; Han Lei; Luo Jingping; Wang Qiang (Jixie chuandong)
The Monte Carlo method is a simple and common way to analyze workspace for robot,and workspace boundary extraction is the key part of Monte Carlo workspace analysis. By using an improved algorithm to extract the workspace boundary of a robot with 7 degrees of freedom,the extraction efficiency and the result both meet the requirement of the following work. The efficiency and accuracy of the improved algorithm are analyzed through experiment,and the result shows the improved algorithm is effective.